Calidad de cuidado en enfermería y nivel de satisfacción percibida por el usuario hospitalizado en el Hospital Leoncio Prado Huamachuco - Romero Santa Cruz, Silvana Maribel (2016)
This descriptive correlational research of sectional cut, was conducted to determine the relationship between quality of nursing care and satisfaction perceived by the hospitalized user of Leoncio Prado Hospital of Huamachuco. The sample consisted of 83 hospitalized patients, selected according to inclusion criterion. Survey Quality nursing care and user satisfaction: to collect data two instruments were used. From the results we reach the following conclusions: The 55.42% of the hospitalized patients receive quality care nursing average, 83.13% of the hospitalized patients are satisfied with the quality of nursing care. There is significant relationship p <0.01 between the quality of nursing care and the level of satisfaction perceived by the hospitalized user in hospitalization service at Leoncio Prado Hospital of Huamachuco.